Impacts of Xingnaojing Injection plus ulinastatin and continuous renal replacement therapy on efficacy, immune function and hemodynamics of septic patients complicated with acute kidney injury - Fang Wen; Shao-kui Si (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the impacts of Xingnaojing Injection plus ulinastatin plus continuous renal replacement therapy （CRRT） on efficacy, immune function and hemodynamics of septic patients complicated with acute kidney injury （AKI）. Methods From May 1, 2019 to May 31, 2022, 104 septic patients complicated with AKI were selected and randomized into two groups of observation （n = 52） and control （n = 52）. Control group received ulinastatin plus CRRT. And observation group had Xingnaojing injection on the basis of control group. Physiological status was evaluated by APACHE Ⅱ score; the levels of T lymphocyte subsets （CD4+/CD8+） were measured by flow cytometry before and after treatment and ratio of CD4+/CD8+ was calculated; the levels of immunoglobulin IgA, IgM and IgG were measured by one-way immunodiffusion before and after treatment; central venous pressure （CVP）, mean arterial pressure （MAP） and heart rate （HR） were monitored with an electronic monitor before and after treatment; in addition, efficacies, changes of APACHE Ⅱ score, CD4+ and CD8+ levels, CD4+/CD8+, IgA/M/G, CVP, MAP and HR were compared between two groups. Results The efficacy of observation group was significantly higher than that of control group （90.39% vs 73.08%, χ2 = 5.216, P = 0.022）. APACHE Ⅱ score of observation and control group declined markedly after treatment [（20.57 ± 3.72） points, （19.74 ± 3.51） points vs （9.67 ± 2.24） points, （13.84 ± 3.11） points] （P＜0.05） and APACHE Ⅱ score of observation group was significantly lower than that of control group after treatment （P＜0.05）. CD4+ level [（30.73 ± 6.54）%, （29.46 ± 6.28）% vs （35.82 ± 6.59）%, （32.65 ± 6.74）%] and CD4+/CD8+ [（1.10 ± 0.24）, （1.12 ± 0.26） vs （1.84±0.31）、（1.52±0.29）] spiked obviously after treatment in observation and control groups. CD8+ level declined markedly [（27.94 ± 5.75）%, （26.30 ± 5.54）% vs （19.48 ± 4.21）%, （21.45 ± 4.54）%] （P＜0.05）.After treatment, the levels of CD4+ and CD4+/CD8+ were significantly higher in observation group than those in control group; CD8+ level was significantly lower than that in control group （P＜0.05）. The levels of IgA [（1.32 ± 0.31） g/L, （1.28 ± 0.29） g/L vs （1.96 ± 0.48） g/L, （1.63 ± 0.42）g/L], IgM [（0.95 ± 0.31） g/L, （0.91 ± 0.28） g/L vs （1.96 ± 0.51） g/L, （1.37 ± 0.36） g/L] and IgG [（5.82 ± 0.81） g/L, （5.77 ± 0.76） g/L vs （9.75 ± 1.43） g/L, （7.32 ± 1.24） g/L] in observation and control groups were significant after treatment. After treatment, the levels of IgA, IgM and IgG were significantly higher in observation group than those in control group （P＜0.05）. The levels of CVP [（6.47 ± 1.24） mmH2O, （6.42 ± 1.21） mmH2O vs （12.83 ± 2.85） mmH2O, （9.54 ± 2.32） mmH2O] and MAP [（56.53 ± 5.34） mmHg, （55.87 ± 5.21） mmHg vs （87.27 ± 6.83） mmHg, （71.92 ± 6.42） mmHg, 1 mmHg = 0.133 kPa] spiked markedly in observation and control groups after treatment. HR declined markedly [（117.56 ± 12.65） beat/min, （115.73 ± 12.57） beat/min vs （83.41 ± 8.73） beat/min, （98.65 ± 10.51） beat/min] （P＜0.05）. After treatment, CVP and MAP levels were significantly higher in observation group than those in control group and HR was significantly lower than that in control group （P＜0.05）. The levels of urea nitrogen [（10.38 ± 2.31） mmol/L, （10.42 ± 2.34） mmol/L vs （14.22 ± 3.34） mmol/L, （19.14±5.27） mmol/L] and serum creatinine [（125.87 ± 26.57） μmol/L, （125.76 ± 25.68） μmol/L vs （183.55 ± 36.81） μmol/L, （241.26 ± 42.79） μmol/L] spiked obviously （P＜0.05）. After treatment, the levels of urea nitrogen and blood creatinine were significantly lower in observation group than those in control group （P＜0.05）. Conclusions Xingnaojing injection combined with ulinastatin and continuous renal replacement therapy are effective in treating patients with sepsis complicated with AKI, which can effectively improve the immune function and hemodynamics of patients, and alleviate the condition of patients.